2011
DOI: 10.1111/j.1365-2591.2011.01896.x
|View full text |Cite
|
Sign up to set email alerts
|

C-shaped root canal system in mandibular second molars in a Chinese population evaluated by cone-beam computed tomography

Abstract: There was high prevalence of C-shaped canals in the mandibular second molars of Chinese population. The canal systems varied considerably in their anatomical configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

41
149
11
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(219 citation statements)
references
References 15 publications
41
149
11
18
Order By: Relevance
“…There is also no statistically significance between the occurrence and age group which implies that age is not a strong determinant on occurrence of C-shaped canal. This is also consistent with what reported by Zheng et al (2011) that the prevalence of C-shaped canal did not differ with age 17 .…”
Section: Discussionsupporting
confidence: 82%
“…There is also no statistically significance between the occurrence and age group which implies that age is not a strong determinant on occurrence of C-shaped canal. This is also consistent with what reported by Zheng et al (2011) that the prevalence of C-shaped canal did not differ with age 17 .…”
Section: Discussionsupporting
confidence: 82%
“…21 In this study, no correlation was found between gender or age and the prevalence of C-shaped canals. These data are similar to the findings of the study by Zheng et al 20 Sert and Bayirli 22 claimed that gender is an important factor to be considered in the preoperative evaluation of canal morphology for root canal treatment; however, the authors evaluated second premolars.…”
Section: Discussionsupporting
confidence: 79%
“…13,14,18 The Chinese population also presented high prevalence of C-shaped canals, as reported by Yang et al, 12 Zheng et al 20 and Zhang et al 5 (32%, 39% and 29%, respectively). C-shaped root and canal configurations were seldom found in Caucasian populations: Cooke and Cox, 1 Weine 7 and Cimilli et al 8 reported a prevalence of 2.7%, 7.6% and 8.1% of C-shaped canals, respectively.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Plenty of document information studied its incidence, morphology and clinical impact [11,12]. It is reported that the prevalence of C-shaped root canals in mandibular second molars was 39% in the Chinese population [13]. Although the occurrence of C-shaped root canals in the maxillary first molars is far less than it in the mandibular second molars, the basic principles are similar when clinicians encounter such cases.…”
Section: Discussionmentioning
confidence: 99%